PEMBUATAN KARYA FOTO STORY DENGAN MENGGUNAKAN PENDEKATAN EDFAT UNTUK FOTOGRAFI KULINER (WARUNG SATE KAMBING TALI ROSO “PAK TRI”) - Hans Hermang Mintana, Sesilia Novita Sari (AKADEMI KOMUNIKASI RADYA BINATAMA, 2022)
ABSTRACT With the shift of culinary mixed with lifestyle, culinary delights in remote areas can become popular. The Klaten specialty Sate Kambing Jumbo Tali Roso Pak Tri, which is located on Jalan Raya Bendogantungan - Bayat, Gadungan Village, Wedi District, Klaten Regency, has been around since the 1990s. However, in recent years his name has just gone viral on social media thanks to the different sizes of satay in general. The subject will be made into a photo story essay. The method used in making the photo story is EDFAT. The EDFAT method is the most suitable method in making this photo story work. Remembering that the creation process requires expertise in assembling visuals that are able to tell a story. This method also requires special precision and sensitivity to objects, subjects and moments in the creation of his works. The process of making this work relies on the use of a Canon 4000D DSLR camera. The creation of this work produces 6 works with detailed methods consisting of 2 photos. Keywords: Photo Story, culinary photography, Klaten, Sate Kambing Jumbo, Photography.